Daidzein ameliorates peripheral neuropathy in Sprague Dawley rats - Laddha, Ankit P.; Kulkarni, Yogesh A. (Frontiers in Pharmacology, 2024)
Neuropathy is the most common disorder comprising peripheral nerve damage in diabetic patients. Prolonged hyperglycaemia and oxidative stress cause metabolic imbalance and are the key reasons for the development of diabetic neuropathy. Daidzein, a soy isoflavone possesses potent anti-hyperglycaemic and antioxidant activity. The present study aims to check the protective effect of Daidzein in diabetic neuropathy in rats. The experimental animal model involved induction of diabetes in rats by intraperitoneal injection of streptozotocin (55 mg/kg).Following confirmation of diabetes, the diabetic rats were subjected to oral treatment with varying doses of Daidzein (25, 50, and 100 mg/kg) and pregabalin (30 mg/kg) for a duration of four weeks, initiated six weeks after diabetes induction. Results indicated that Daidzein treatment led to a significant reduction in plasma glucose levels and an improvement in body weight among diabetic animals. Moreover, Daidzein demonstrated a positive impact on sensory functions, as evidenced by the effect on tail withdrawal and response latency. Mechanical hyperalgesia and allodynia, common symptoms of diabetic neuropathy, were also significantly reduced with both Daidzein and pregabalin treatment. Notably, nerve conduction velocities exhibited improvement following the administration of Daidzein and pregabalin.Further investigation into the molecular mechanisms revealed that Daidzein treatment resulted in a notable enhancement of antioxidant enzyme levels and a reduction in the overexpression of NOX-4 in the sciatic nerve. This suggests that Daidzein's therapeutic effect is associated with the inhibition of oxidative stress via NOX-4.In summary, the findings of study suggests that, Daidzein treatment significantly attenuated diabetic neuropathy by inhibiting oxidative stress via NOX-4 inhibition.